Pengaruh Latihan Keseimbangan Dengan Trampolin Terhadap Peningkatan Keseimbangan Pada Pemain Skateboard - Putra, Andre Dwi Karna; , Dwi Rosella Komala Sari , S.St FT., M.Fis (2017)
Background: Skateboard sport in Indonesia which is developing gives an opportunity to an individual to have an achievement. Little knowledge on increasing the basic ability to play skateboard influences the decrease in the achievement. The influence of trampoline had been proved using a practice of trampoline which has an increase in the balance, mobility, and activity. On of exercise programs to increase the balance is by trampoline practice. Therefore, the researcher was interested in conducting a research on the influence of balancing using trampoline on the increase of balance in the skateboard players. Purpose: The purpose of this research is to know the presence of influence of the balancing practice using trampoline on the increase of balance in the skateboard players. Method: Type of this research is Quasy experiment using a method of pre-test and post-test with control group design. Respondents consisted of 20 people divided into two groups: 10 people with a treatment (providing a trampoline practice) and 10 people of control (without practice). The research was conducted for 4 weeks using 3 times practice per week. The measurement of balance was conducted once in the time of pre-test and post-test by using strok stand test as the measurement. The data analysis used the Wilcoxon test and Mann-Whitney test. Results: The results of the research on the influence on the treatment group using pre and post test revealed an increase in the balance in which p = 0.026, therefore, there is an influence of trampoline practice on the increase in the balance. Meanwhile, a test of influence difference between the treatment group and the control group obtained p = 0.005. The results of balance in the treatment group before and after the treatment is 1.6 second. Conclusion: There is an influence of balancing practice using trampoline on the increase in the balance of skateboard players. Keywords: Balance, Trampoline, Skateboard